Subclinical Atherosclerosis in Behçet's Disease - Samia HASSAN,; Tamer GHEITA,; Shada GHONEIM,; Loi NASR2, (Archives of Rheumatology, 2012)
Objectives: This study aims to assess the carotid intimamedia thickness (IMT) and plaque formation in patients with Behçet's disease (BD) by Doppler ultrasonography (US) and to correlate it with disease activity, and clinical and laboratory parameters. Patients and methods: Thirty BD patients (25 males and 5 females; mean age 35.8±8.7 years; 22 to 54 years) diagnosed according to the new set of diagnostic criteria published by the International Study Group for Behçet's Disease, were recruited from the Rheumatology Department, Cairo University Hospitals. The mean disease duration was 8.7±5.9 years. Subjects with diabetes mellitus, hypertension or evidence of myocardial infarction were excluded. Full history taking, clinical examination and skin pathergy test were carried out for all patients. Laboratory measurements including lipid profile were also performed for both patients and controls. Disease activity was assessed using the Behçet's Disease Current Activity Form (BDCAF). Carotid artery ultrasonography was carried out. Results: The mean IMT was significantly different in the patient group, compared to controls (p=0.003). The mean IMT was significantly correlated with urea, creatinine, cholesterol, triglycerides and the BDCAF, while it was inversely associated with HDL level. Atherosclerotic plaque was found in five patients (16.7%). Conclusion: A morphologic evidence of subclinical atherosclerosis in patients with BD is verified. Renal function in these patients may indicate possible risks and BDCAF score may significantly suggest cardiovascular involvement.